Identifikasi Faktor yang Mempengaruhi Data Driven Decision pada Pemerintah Desa Menggunakan SEM GSCA - Nisa Athira; Marizsa Herlina (Jurnal Riset Statistika, 2022)
Abstract. SEM GSCA (Structural Equation Modelling Generalized Structured Component Analysis) is a method that complements the lack of SEM PLS because it does not provide mechanism to assess overall goodness of fit, it is difficult to determine how well the model fits to data and compare it with model alternative. Meanwhile, SEM GSCA offers global least square optimization criteria to minimize estimation of model parameters and model relationships by minimizing residuals using ALS (Alternating Least Square), it can detect how well the size of model is involved in research. In this study, SEM GSCA was used to identify the factors that influence data driven decision in Village Government. Data driven decision is a decision making based on actual data or observations. Variables of data quality, tool sophistication, analytical skills and bigness of data are the suspected factor that have influence on decision making quality. Samples were taken using purposive sampling with questionnaires to 52 Apparatus who met the criteria for Independent Villages in Ciamis. Based on results, there are positive and significant influence between data quality, tool sophistication and analytical skills on decision making quality. Meanwhile, bigness of data variable has a negative and insignificant effect on decision making quality. Abstrak. SEM GSCA menawarkan kriteria global least square optimization untuk meminimumkan estimasi parameter model dan mengevaluasi model hubungan dengan meminimumkan residual atau galatnya menggunakan ALS (Alternating Least Square), sehingga GSCA dapat mengidentifikasi seberapa baik model pengukuran terlibat dalam penelitian. Dalam penelitian ini, SEM GSCA digunakan untuk mengidentifikasi faktor-faktor yang mempengaruhi data driven decision pada Pemerintah Desa. Data driven decision merupakan pengambilan keputusan yang didasarkan pada data aktual atau hasil pengamatan. Dalam penelitian diduga variabel kualitas data, kecanggihan alat, kemampuan analisis dan data yang besar berpengaruh terhadap kualitas pengambilan keputusan. Sampel diambil dengan teknik purposive sampling dengan membagikan kuisioner pada 52 aparatur Desa yang memenuhi kriteria Desa Mandiri di Kabupaten Ciamis. Berdasarkan hasil analisis diperoleh bahwa terdapat pengaruh yang positif dan signifikan antara variabel kualitas data, kecanggihan alat dan kemampuan analisis terhadap kualitas pengambilan keputusan. Sedangkan pada variabel data yang besar terdapat pengaruh yang negatif dan tidak signifikan terhadap kualitas pengambilan keputusan.